First Volcanic Plume Measurements by an Elastic/Raman Lidar Close to the Etna Summit Craters - Boselli, Antonella; Scollo, Simona; Leto, Giuseppe; Sanchez, Ricardo Zanmar; Sannino, Alessia; Wang, Xuan; Coltelli, Mauro; Spinelli, Nicola (Frontiers in Earth Science, 2018)
From 14 to 17 December 2013, Mt. Etna, in Italy, showed an intense Strombolian activity from the New South East Crater (NSEC). Lidar measurements were performed in Catania, pointing at a thin volcanic plume, clearly visible and dispersed from the summit craters toward the South East. Real-time Lidar observations captured the complex dynamics of the volcanic plume along with the pulsatory nature of the explosive activity and allowed to analyze the geometrical, optical and microphysical properties of the volcanic ash. Both the aerosol backscattering (βA) and the extinction coefficient (αA) profiles at 355nm, and their ratio (the Lidar Ratio - LR) were measured near the volcanic source using an Elastic/Raman Lidar system. Moreover, calibrated particle linear depolarization values (δA) were obtained from the Lidar profiles measured in the parallel and cross polarized channels at 355nm, thus allowing to characterize the particle shape. The βA, LR and δA values were used to estimate the ash concentration (γ) profiles in the volcanic plume. This is the first study of optical properties of volcanic particles through Elastic/Raman measurements at Etna volcano.